Prebiotic and Synbiotic Modifications of Beta Oxidation and Lipogenic Gene Expression after Experimental Hypercholesterolemia in Rat Liver - Alves, Claudia C.; Waitzberg, Dan L.; de Andrade, Laila S.; dos Santos Aguiar, Laís; Reis, Milene B.; Guanabara, Camila C.; Júnior, Odair A.; Ribeiro, Daniel A.; Sala, Priscila (Frontiers in Microbiology, 2017)
Background and aims: Non-alcoholic fatty liver disease (NAFLD) is characterized by the presence of fat in hepatocytes because of decreased ß-oxidation and increased lipogenesis. Prebiotics, probiotics, and synbiotic have modulatory effects on intestinal microbiota and may influence the gut-liver axis. Our aim was to evaluate the effects of prebiotic, probiotics, and synbiotic on liver histopathology and gene expression related to ß-oxidation and lipogenesis after hypercholesterolemia. Methods: Wistar male adult rats (n=40) were submitted to hypercholesterolemic conditions (HPC) (60 days). On Day 30 of HPC, rats were subdivided in 5 groups: negative control (NC): without HPC + Gv (distilled water); positive control (PC): with HPC + Gv (distilled water); prebiotic (PRE): HPC + Gv with prebiotic (Fiber FOS®); probiotic (PRO): HPC + Gv with probiotic strains Gv (Probiatop®); and synbiotic (SYN): HPC + Gvwith synbiotic (Simbioflora®). All rats were sacrificed on Day 30 post-treatment. Blood was collected to verify total serum cholesterol, and liver tissue was sampled to verify histopathological changes and gene expression. Gene expression related to ß-oxidation (PPAR-α and CPT-1) and lipogenesis (SREBP-1c, FAS and ME) was evaluated in liver tissue using RT-qPCR. Results: PC had higher cholesterol levels when compared to NC. PRE and SYN rats had lower cholesterol levels than PC . PC rats showed more histopathological changes than NC rats; PRE and SYN rats showed fewer alterations than PC rats. PPAR-α was expressed at higher levels in SYN and PC rats compared with PRE and PRO rats. CPT-1 expression was similar in all groups. SREBP-1c was expressed at higher levels in PC rats compared with NC rats; levels were lower in SYN rats compared with PRO rats; levels were lower in PRE rats compared with PC and PRO rats. FAS was expressed at lower levels in PRE rats compared with SYN rats. ME expression was lower in PC rats compared with NC rats. Conclusions: Prebiotic and synbiotic supplementation improve hepatic alterations related to hypercholesterolemia. These changes appear to be mediated by altered expression of genes related to ß-oxidation and lipogenesis.